Avenue 5. The complete first season [videorecording (DVD)] - Iannucci, Armando, 1963- (HBO, 2020)
The troubled crew of Avenue 5, a space cruise ship filled with spoiled, rich, snotty space tourists, must try and keep everyone calm after their ship gets thrown off course into space and ends up needing three years to return to Earth.